2007
DOI: 10.17221/2060-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with subclinical mastitis in dairy cows on Swiss organic and conventional production system farms

Abstract: Epidemiological studies comparing risk factors for subclinical mastitis (SM) in organic (OP) and conventional dairy production systems (CP) are lacking. In 60 OP and 60 CP farms, 970 cows were used to study risk factors for SM at 31 days postpartum. Cows showing a positive (≥ 1+) California Mastitis Test (CMT) in at least one quarter, but without clinical symptoms, were classified SM-positive. For OP cows increased (<I>P</I> < 0.05) odds ratios (OR) for SM were found for other than Simmental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
2
23
1
1
Order By: Relevance
“…In fact, it is likely that the opposite is actu-ally the case, and it is reasonable to assume that these farms are those with inherent mastitis problems and have increased their testing regimen to improve mastitis detection. Similar results have been reported for freestalls in Switzerland, where the mastitis incidence risk ratio was lower (0.61, P = 0.01) when bacteriological cultures were reportedly never done compared with the reference value of always or occasionally done (Gordon et al, 2013) and in a further Swiss study where subclinical mastitis was less likely to occur on farms with a moderate compared with good level of hygiene (Doherr et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, it is likely that the opposite is actu-ally the case, and it is reasonable to assume that these farms are those with inherent mastitis problems and have increased their testing regimen to improve mastitis detection. Similar results have been reported for freestalls in Switzerland, where the mastitis incidence risk ratio was lower (0.61, P = 0.01) when bacteriological cultures were reportedly never done compared with the reference value of always or occasionally done (Gordon et al, 2013) and in a further Swiss study where subclinical mastitis was less likely to occur on farms with a moderate compared with good level of hygiene (Doherr et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have been reported in other studies of udder health in small dairy farms. For example, a Finnish study (largest herd size category: >60 cows) reported average herd size as having no effect on subclinical mastitis (OR = 1.003), whereas a Swiss study found that a herd size of >27 dairy cows and heifers increased the odds of subclinical mastitis occurring compared with smaller herds (<20 head; Doherr et al, 2007;Hiitiö et al, 2017). Dairy farms in other European countries often have much larger herds, with surveys from 2016 to 2017 reporting a mean of 61.9 cows per herd in Germany, 93.8 cows per herd in the Netherlands, and 146 cows per herd in the United Kingdom compared with just 21.3 cows per herd in Austria at that time (Barkema et al, 2015;AHDB Dairy, 2018;BMEL Statistik, 2018;CRV, 2018;ZAR, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased albumiu couceutratiou was ouly at d 21 postpartum and may indicate that scEndo cows were responding to mild inflammation because albumin is decreased in response to the production of acute-phase proteius (Fleck, 1989;Bertoui et al, 2008) aud prolouged chauge in albumin concentration occurs after an inflammatory event (Nicholson et al, 2000). Greater milk albumin concentration is also associated with a reduced risk of subcliuical mastitis (Doherr et al, 2007) and several studies ideutified a positive associatiou of milk proteiu couteut with iucreased submission rate and pregnancy rate to first service (Morton, 2000;Buckley et al, 2003).…”
Section: A)mentioning
confidence: 99%
“…Limited information is available in the literature comparing the mastitis prevalence in organic and conventional systems worldwide, however, in contrast to some inconsistencies among studies when comparing SCC, virtually all studies have reported fewer cases of clinical mastitis for organic when compared to conventional farms (for review see Ruegg, 2009). A completely different scenario has been observed for the subclinical mastitis, which is assumed to be a frequent problem in organic farming (Krutzinna et al, 1997;Weller & Davies, 1998;Busato et al, 2000;Fehlings & Deneke, 2000;Hovi & Roderick, 2000;Zwald et al, 2004;Roesch et al, 2006Roesch et al, , 2007Doherr et al, 2007). Environmental pathogens are generally associated with higher percentages of clinical mastitis than contagious pathogens (Bradley et al, 2007).…”
Section: Intramammary Infection Dynamicsmentioning
confidence: 99%